2022
DOI: 10.2147/jmdh.s375567
|View full text |Cite
|
Sign up to set email alerts
|

Management of Low Back Pain in Primary Health-Care Settings: Physician’s Awareness and Practices Based on Red Flags

Abstract: Background: Low back pain (LBP) is one of the most common health problems. Red flags (RFs) of LBP are risk factors that are reported during clinical assessment to determine serious illness. This study aimed to assess primary health-care physicians' knowledge of and practices for RFs of LBP and identify variables associated with a high level of knowledge and awareness about it. Methods: An observational cross-sectional survey was conducted in 2021 among a random sample of 261 primary health care (PHC) physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Fifteen studies ( n = 15) reported that clinician characteristics influence imaging CDM (Arishy et al., 2022; Barnett et al., 2020; Bouck et al., 2019; Bussières et al., 2013; de Zoete et al., 2022; Dietrich et al., 2018; Ganesh et al., 2022; Gidwani et al., 2016; Graves et al., 2012; Hong et al., 2017; Le et al., 2018; Learman et al., 2014; Sears et al., 2016; Tan et al., 2016; Zargar et al., 2014). Clinician characteristics were divided into six subcategories: age ( n = 1; 7%) sex ( n = 1; 7%), experience (years) ( n = 5; 33%), education ( n = 4; 27%), role ( n = 8; 53%) and clinical practice ( n = 6; 40%) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies ( n = 15) reported that clinician characteristics influence imaging CDM (Arishy et al., 2022; Barnett et al., 2020; Bouck et al., 2019; Bussières et al., 2013; de Zoete et al., 2022; Dietrich et al., 2018; Ganesh et al., 2022; Gidwani et al., 2016; Graves et al., 2012; Hong et al., 2017; Le et al., 2018; Learman et al., 2014; Sears et al., 2016; Tan et al., 2016; Zargar et al., 2014). Clinician characteristics were divided into six subcategories: age ( n = 1; 7%) sex ( n = 1; 7%), experience (years) ( n = 5; 33%), education ( n = 4; 27%), role ( n = 8; 53%) and clinical practice ( n = 6; 40%) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…(Not) having prior treatment or imaging (Zargar et al, 2014). Logistics: Time arrived and duration spent at clinic (Ferreira et al, 2019), prevalence of observation/treatment room use (Schlemmer et al, 2015), year of appointment (Barnett et al, 2020) Clinician characteristics Age Age (Barnett et al, 2020) Sex Sex (Bussières et al, 2013) Experience (years) Years (Bussières et al, 2013;de Zoete et al, 2022;Learman et al, 2014;Sears et al, 2016;Tan et al, 2016) Education Level of qualification (de Zoete et al, 2022;Ganesh et al, 2022), school (Bussières et al, 2013) or country (Tan et al, 2016) in which qualification was obtained Role Title/discipline (Arishy et al, 2022;Barnett et al, 2020;Bouck et al, 2019;Dietrich et al, 2018;Gidwani et al, 2016;Graves et al, 2012;Tan et al, 2016;Zargar et al, 2014),…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Research in this area has focused predominantly on the broader aspects of cardiovascular risk, such as the prevalence of traditional risk factors such as hypertension, diabetes, and dyslipidemia in individuals with bipolar disorder. [ 3 ] There has been less emphasis on the direct assessment of cardiac function using advanced techniques such as echocardiography, particularly in terms of myocardial strain. Myocardial deformation, a parameter that provides information on cardiac muscle deformation during the cardiac cycle, is an important indicator of myocardial function and has been associated with various cardiac pathologies.…”
Section: Introductionmentioning
confidence: 99%